2014
DOI: 10.1111/jop.12154
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying Cystic Odontogenic Tumour: immunohistochemical expression of matrix metalloproteinases, their inhibitors (TIMPs and RECK) and inducer (EMMPRIN)

Abstract: We concluded that these proteins/enzymes are differentially expressed in both epithelium and stroma of CCOT, suggesting an imbalance between MMPs and their inducer/inhibitors may contribute on the tumour behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
1
2
1
Order By: Relevance
“…A low level of expression increased the rates of tongue cancer invasion and metastasis, and the regulation may be related to an inhibitory mechanism of RECK on MMP-2 and MMP-9 expression (34). RECK shows an obviously negative correlation with MMP-2 and MMP-9 expression, suggesting that in the process of tumor invasion and metastasis, the expression of RECK is downregulated, limiting the inhibition of RECK on MMP-2 and MMP-9, thus achieving invasion and metastasis of tumor tissues (35). The present study first demonstrated that icariin increased the RECK protein expression level in ovarian cancer A2780 cells.…”
Section: Discussionsupporting
confidence: 55%
“…A low level of expression increased the rates of tongue cancer invasion and metastasis, and the regulation may be related to an inhibitory mechanism of RECK on MMP-2 and MMP-9 expression (34). RECK shows an obviously negative correlation with MMP-2 and MMP-9 expression, suggesting that in the process of tumor invasion and metastasis, the expression of RECK is downregulated, limiting the inhibition of RECK on MMP-2 and MMP-9, thus achieving invasion and metastasis of tumor tissues (35). The present study first demonstrated that icariin increased the RECK protein expression level in ovarian cancer A2780 cells.…”
Section: Discussionsupporting
confidence: 55%
“…In certain localities they were grouped forming large areas of eosinophilic and acellular material. Although the literature says that it is possible to observe mineralized material similar to dentin 14 , in our case, the mineral product was in form of a dystrophic mineralization.…”
Section: Discussioncontrasting
confidence: 53%
“…[4][5][6] During AME progression, mitogens are randomly released and promote the secretion of matrix metalloproteinases (MMPs) that induce localized proteolysis of the extracellular matrix. 4,5,7 Recent studies have revealed that localized proteolysis is mediated by invadopodia, 8,9 which are finger-like cellular protrusions that have intrinsic proteolytic activity and are associated with early tumour invasion and activation of MMPs. 10,11 Cortactin and membrane type 1 MMP (MT1-MMP) have been described in AME.…”
Section: Introductionmentioning
confidence: 99%